Antioxidant activity of phenolic compounds added to a functional emulsion containing omega-3 fatty acids and plant sterol esters. (1st September 2015) - Espinosa, Raquel Rainho; Inchingolo, Raffaella; Alencar, Severino Matias; Rodriguez-Estrada, Maria Teresa; Castro, Inar Alves
Highlights: Functional emulsions containing omega 3 fatty acids and plant sterols can oxidise. The antioxidant action of natural compounds was evaluated in a functional emulsion. Sinapic acid and rutin obtained from propolis showed the highest antioxidant action. The combination of ascorbic acid and iron promoted the oxidation at room temperature. β-Sitosterol oxidised in a higher proportion than campesterol and stigmasterol. Abstract: The effect of eleven compounds extracted from red propolis on the oxidative stability of a functional emulsion was evaluated. Emulsions prepared with Echium oil as omega 3 (ω-3 FA) source, containing 1.63 g/100 mL of α-linolenic acid (ALA), 0.73 g/100 mL of stearidonic acid (SDA) and 0.65 g/100 mL of plant sterol esters (PSE) were prepared without or with phenolic compounds (vanillic acid, caffeic acid, trans -cinnamic acid, 2, 4-dihydroxycinnamic acid, p -coumaric acid, quercetin, trans -ferulic acid, trans, trans -farnesol, rutin, gallic acid or sinapic acid). tert -Butylhydroquinone and a mixture containing ascorbic acid and FeSO4 were applied as negative and positive controls of the oxidation. Hydroperoxide, thiobarbituric acid reactive substances (TBARS), malondialdehyde and phytosterol oxidation products (POPs) were evaluated as oxidative markers. Based on hydroperoxide and TBARS analysis, sinapic acid and rutin (200 ppm) showed the same antioxidant activity than TBHQ, representing a potential alternative as natural antioxidant to be applied in a functional emulsion containing ω-3 FA and PSE.